Fatigue Properties Estimation and Life Prediction for Steels under Axial, Torsional, and In-Phase Loading - Ernian Zhao; Qiang Zhou; Weilian Qu; Wenming Wang (Advances in Materials Science and Engineering)
In this study, several estimation methods of fatigue properties based on different monotonic mechanical parameters were first discussed. The advantages and disadvantages of the Hardness Method proposed by Roessle and Fatemi were investigated and improved through the analysis of a total of 92 fatigue test data. A new Segment Fitting Method from Brinell hardness was then proposed for the fatigue properties estimation, and a total of 96 pieces of fatigue test data under axial, torsional, and multiaxial in-phase loading were collected to verify the applicability of the new proposal. Finally, the prediction accuracy of the new proposal and three exciting estimation methods was compared with the predictions based on the experimental fatigue properties. Based on the results obtained, the newly proposed estimation method has a significant improvement on the relation between fatigue ductility coefficient and Brinell hardness, which consequently improves the fatigue life prediction accuracy with the scatter band of 2, particularly for the materials with low Brinell hardness. The present study can provide a simplified analysis of the preliminary fatigue design of engineering structures.